KOMUNIKASI WIDYAISWARA DAN GURU DALAM MENGEVALUASI DIKLAT PENINGKATAN KOPETENSI PEMBELAJARAN PADA PUSAT PENGEMBANGAN DAN PEMBERDAYAAN PENDIDIK DAN TENAGA KEPENDIDIKAN - Floren Kembaren; Elisabeth Sitepu (MESSAGE: JURNAL KOMUNIKASI, 2020)
The phenomenon faced by teachers is that most teachers today do not understand the curriculum well, so there are clear obstacles in the implementation of the learning process in the classroom. The teacher's understanding in the field can be identified from the training activities material including the Concept and Deepening of HOTS-Oriented Learning Materials, and HOTS-Oriented Learning Development, most teachers have difficulty connecting Core Competencies, Basic Competencies and Indicators to be achieved. The research objectives are: To find out how Widyaiswara and Teacher's Communication about Education and Training Competency Improvement Training in the Center for Development and Empowerment of Educators and Education Personnel in the Field of Building and Electricity in Medan. To analyze how to evaluate the Training of Learning Competency Improvement at the Center for Development and Empowerment of Educators and Education Personnel in the Field of Building and Electricity in Medan. To find out how Widyaiswara and Teacher Communication efforts are in Evaluating Education and Training Competency Improvement Training at the Center for Development and Empowerment of Educators and Education Personnel in the Field of Building and Electricity in MedanIn terms of communication carried out by widyaiswara both with group communication with the teachers, a widyaiswara as a communicator in the implementation of training delivered by widyaiswara to the training participants had good communication. In the evaluation conducted by P4TK Medan through widyaiswara, it has been going well, it is proven that the participants of PKP training are able to achieve good grades and have certificates. Communication Efforts of Widyaiswara and Teachers in Evaluating the Training of Improvement of Learning Competencies at the Center for Development and Empowerment of Educators and Education Personnel in the Field of Building and Electricity in Medan are zoning systems and socialization of learning houses.